Big data in safety management: An overview. (November 2021) - Wang, Bing; Wang, Yuanjie
Highlights: Big data has an important influence on safety management in various fields. Reviewed the general theories and technologies of big data in safety management. Summarized the typical applications of big data in safety management according to different fields. Discussed the challenges of big data in safety management and its future development directions. Abstract: Big data has an important influence on safety management in various fields where its applications are becoming more prevalent. The analysis results of big data have become an important reference influencing safety decision-making. Realizing the promising benefits of big data in safety management has motivated us to write a review on the influence of big data and its applications in safety management. This study also investigates the challenges faced by big data in safety management and provides insights to future directions for research and practice. We first briefly introduce the development history of big data and its influence on safety management. We then review the general theories and technologies of big data in safety management. Finally, we summarize the typical applications of big data in safety management according to different fields. Additional findings from the review process are also presented.